ANALISIS RETORIKA VISUAL KARIKATUR MAJALAH TEMPO EDISI 02 JUNI 2024 ”TAPERA: TAK PUNYA PERASAAN” - Manalu, Arafat; Siregar, Angel Marta; Zainy, Rafiqah; Tambunan, Silvia Yulandari; Lubis, Malan (PT. Intelek Cendikiawan Nusantara, 2024)
Karikatur Majalah Tempo